MEASURING THE EFFECT OF FOREIGN CURRENCY WINDOW SALES ON THE INFLATION RATE IN IRAQ FOR THE PERIOD (2004-2020) (World Economics and Finance Bulletin, 2023)
The research aims to measure the impact of the foreign currency sales window on the inflation rate in Iraq, and the foreign currency sales window is considered one of the important tools that are used in rentier economies, including Iraq, in order to curb inflation by maintaining the general level of prices . In order to measure the effect of currency window sales on the inflation rate, the study used the study methodology and the study used the nonlinear autoregressive distributed lag (nonlinear autoregressive distributed lag) methodology. The study concluded that an increase in foreign currency sales by one million dollars in the short term leads to a decrease in the inflation rate by 0.94%. The study also concluded that an increase in foreign currency sales by one million dollars in the long term leads to a decrease in the inflation rate by 0.74%. The currency window of the dollar and the use of foreign reserves as a tool to face crises and preserve it for the purpose of saving subsequent generations from the internal and external problems that the Iraqi economy is exposed to, and not to deplete, waste and leak financial resources abroad in the form of consumer imports, but must work to invest them in establishing infrastructure and preparing economic sectors Especially the private sector.
Keywords: foreign currency window; inflation rate; exchange rate